Formação e qualificação de pequenos produtores rurais: a experiência da Coordenadoria de Assistência Técnica Integral - CATI - Botiglieri, Monica Fernanda (Universidade Federal de São Carlos, 2012)
This research has the aim to present the investigation made about the Coordination of Integral Technical Assistance CATI, an agency that is part of the Agriculture and Supply Secretary in the state of São Paulo. This agency works with all kind of technical assistance to rural workers, specially small farmers. We tried to realize how this institution has been organized since its creation and what they have been doing for the education of these people. Some projects made with rural settlements were also described. Using visits, interviews and other ways of research we hope to have been able to show their activities as well as their limitations.
Keywords: Educação; Educação do campo; Pequenos produtores rurais; Trabalhadores rurais; Small farmers; Rural work; Rural education; CIENCIAS HUMANAS::EDUCACAO